2019
DOI: 10.1097/md.0000000000017166
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of low-level laser therapy on muscle fatigue of the biceps brachii muscle of healthy individuals and spastic individuals

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This is partly because there are many contributing factors to PSF 8 , 10 – 32 , and each research team may focus only on some of the factors to find a route for preventing, treating or managing PSF. Any endeavour to find the most effective intervention in the research literature leads to a collection of heterogeneous interventions from physiotherapy 33 and exercise 34 – 38 to psychotherapy, pharmacotherapy, and recently laser therapy 39 41 .…”
Section: Introductionmentioning
confidence: 99%
“…This is partly because there are many contributing factors to PSF 8 , 10 – 32 , and each research team may focus only on some of the factors to find a route for preventing, treating or managing PSF. Any endeavour to find the most effective intervention in the research literature leads to a collection of heterogeneous interventions from physiotherapy 33 and exercise 34 – 38 to psychotherapy, pharmacotherapy, and recently laser therapy 39 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of LED to the masticatory muscles affects the local tissues around the light application site and previous studies have shown the effectiveness of LED treatment in muscle tissues [ 26 , 27 , 28 ]. The literature also reports that it is possible to observe systemic responses through light therapy, with the action of deep light stimulation directly on the brain [ 29 ].…”
Section: Discussionmentioning
confidence: 99%